Gardening in Raised Beds - Terry Brite DelValle (EDIS)
Gardening in raised beds is becoming more popular as more people try growing their own food. Using raised beds is like growing plants in large containers. The planting area is raised above the existing soil level and usually enclosed within a structure to form a planting bed. This 3-page fact sheet was written by Terry Brite DelValle, and published by the UF Department of Environmental Horticulture, May 2013.